WHICH ONE IS MORE ESSENTIAL FOR SECOND LANGUAGE LEARNERS: INSTRUMENTAL OR INTEGRATIVE MOTIVATION? - Syarifuddin, Syarifuddin (Universitas Yudharta Pasuruan, 2014)
There are some major factors which influence second language learning. Motivation is an important factor that determines the success of learners of Arabic or English as second language. There are two types of motivation: Instrumental motivation and integrative motivation. The instrumental motivation is the desire to achieve the goals from the study of a language without having opportunity or chance to use the target language with members of the target community. In contrast, the integrative motivation refers to language learners that interact with members of the target language group, and refers to language learners who admire the country and the culture of target language. This essay will compare and contrast both types of motivation.Â  This essay, then, argues that instrumental motivation is more important than integrative motivation. This is because of some reasons. For example, meeting the requirements of school or university, getting good grades, passing the exam, looking for a job or looking for higher salary job based on foreign language skills, etc.